(3NWC GdeVQhQ h CKQg Ydi JbOjQ GdJYhjV (B: s (3OQGSI ebGQfI aj GdbGfhf GdeOfj Gdjefj h GdeUQj h Gdabg GdESdGej (B/ s - (3eLGgO fGUQ SYjO GdLHQjs; (3SYjO SdjeGf LHQs; (3eMeO fLjH YhVjf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3JfGhdJ gPg GdOQGSI eaghe GdNWC h GdeYjGQ GdPj jbGS Hg Pdc GdNWC aj cd ef GdbGfhf GdeOfj h Gdabg GdESdGej (B: (3Ke MOOJ GdebUhO HNWC GdeVQhQ (B: (3h GdaQb Hjfg h Hjf GdeLfj Ydjg (B: (3h eGgj GdTQhW GdhGLH JhGaQgG aj NWC GdeVQhQ (B: (3h cPdc GdMGdGJ GdJj jTJQc Ch jSGge ajgG GdeVQhQ HhbhY GdaYd GdVGQ aj GdeSFhdjJjf GdJbUjQjI h GdYbOjI (B. (3ceG HjfJ GdOQGSI cPdc ebOGQ GdJYhjV aj GdMGdGJ GdJj jTJQc ajgG cd ef GdeSFhd h GdeVQhQ aj EMOGK GdVQQ (B: (3h GdCgejI GdJj jJQJH YdjgG GdQVGA GdUGOQ ef GdeVQhQ HhbhY GdVQQ eeG jDKQ Ydi Mbg aj ebOGQ GdJYhjV GdPj jSJMbg HSHH eTGQcJg Ch QVGAg HhbhY GdVQQ Ydi faSgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2013s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B535-580s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GTJQGc NWC GdeVQhQs; (3JCKjQ NWC GdeVQhQs; (3NWC GdeVQhQs; (3GdhGbYI GdEQGOjI GdVGQI s; (3EKHGJ NWC GdeVQhQ s; (3YdGbI GdSHHjI s; (3eSFhdjI GdWHjH s; (3GdeSFhdjI GdTjFjI s; (3GdXQha GdedGHSIs; (3GdahGFO GdJCNjQjI s; (3ebOGQ GdJYhjV s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs